Effects of the cropyear and the agronomical factors on agronomical elements of different sweet corn (Zea Mays L. convar. saccharata Koern.) genotypes in long-term experiment - Lente, Ádám (Acta Agraria Debreceniensis, 2012)
In the crop season of 2010 (rainy year), we studied the effect of three agrotechnical factors (sowing time, fertilization, plant density) and four different genotypes on the agronomical characteristics of sweet corn on chernozem soil in the Hajdúság. The experiments were carried out at the Látókép Experimental Farm of the University of Debrecen. In the experiment, two sowing dates (27 April, 26 May), six fertilization levels (control, N30+PK, N60+PK, N90+PK, N120+PK, N150+PK) and four genotypes (Jumbo, Enterprise, Prelude, Box-R) were used at two plant densities (45 thousand plants ha-1, 65 thousand plants ha-1). The amount of precipitation in the season of 2010 was 184 mm higher, while the average temperature was 0.8 oC higher in the studied months than the average of 30 years. Weather was more favourable for sweet maize at the first sowing date, if we consider the yields, however, if we evaluate the agronomical data and yield elements (number of cobs, cob length and diameter, the number of kernel rows, the number of kernels per row) it can be stated that the size of the fertile cobs was greater at the second sowing date due to the lower number of cobs. The largest number of fertile cobs was harvested in the case of the hybrid Enterprise (72367.9 ha-1) in the higher plant density treatment (65 thousand ha-1) at the fertilization level of N120+PK when the first sowing date was applied. The largest cobs were harvested from the hybrid Box-R (cob weight with husks: 516.7 g, number of kernels in one row: 45.7) at the lower plant density (45 thousand plants ha-1) in the second sowing date treatment. Cob diameter and the number of kernel rows were the highest for the hybrid Prelude.